Construction of a scale on beliefs of high school teachers about the reform of mathematics education in Costa Rica: Construcción de una escala sobre creencias de docentes de educación media acerca de la reforma de la educación matemática en Costa Rica - Monge Madriz, Carlos A. (2020)
The results of preparing and validating a Likert-type scale for measuring the beliefs of secondary school teachers on the math study programs approved by the Higher Education Council of Costa Rica in 2012 are presented as a component of the research project “Mathematical education reform in Costa Rica. Evaluation of progress after three years of its application and belief systems of teachers on the reform” (REMEYC).The preliminary version of the scale was subjected to a content validation process through the technique of expert judgment, with the participation of specialists in educational mathematics from the School of Mathematics of the Technological Institute of Costa Rica. Subsequently, a pilot test was carried out with the participation of 51 mathematics teachers from public schools. With the data collected, a study of the psychometric properties of the scale was carried out, by calculating the index of discrimination of the items, the analysis of the unidimensionality using techniques of factor analysis and the establishment of reliability by applying the Cronbach’s alpha technique. Based on the results of the psychometric study, the final version of the scale consisting of 20 items was formed.